The Influence of Applying the Principles of Experiential Coyote Drama (ECD) Methods in Teaching English Language from the English language supervisor’s perspectives in Jenin city (case study). - Barahmeh, Mosaddaq; Bsharat, Tahani (Advances in Social Sciences Research Journal, 2021)
This paper sheds light on the importance of applying the Principles of Experiential Coyote Drama (ECD) Methods in Teaching English Language from the English language supervisor’s perspectives in Jenin city (case study). First of all, this paper discloses the Coyote teaching method. Later, this paper also explains the importance of Experiential learning in teaching English as a Foreign Language. It also explains the educational drama and its techniques in teaching-learning the English language. Finally, this paper suggests a new teaching-learning method which is Experiential Coyote Drama (ECD). All in all, from the previous studies and researches the researchers found that mixing educational drama with Experiential learning and Coyote method will bring a full package of new methods and activities for the teachers, learners and future researchers in teaching English as a Foreign Language.